Relevansi Pemikiran Ekonomi Muhammad Baqir Ash-Sadr - Muhammad Kambali (Universitas Islam Lamongan, 2018)
The failure of the capitalist system in realizing just welfare becomes a necessity for mankind to deconstruct the economy of capitalism into a just and civic economic system which in this case of course Islamic economics deserves to be considered as one alternative in realizing human prosperity. As one of today’s contemporary muslim economists, Baqir Sadr’s ideas are increasingly finding relevance to the current global economic situation. This article examines the thoughts of Baqir Sadr in the book Iqtishaduna (our Economic) by using the approach of library research. The results of this study include. First The idea that capitalism is a system that is solely oriented to the accumulation of capital and ignore the values outside the economic motive. The two important meanings of the State’s role in economics at Baqir Sadr’s foundation can be found in the notion of a conventional economist, one of which is former US Federal Reserve governor Alan Gleenspan, which highlights the importance of state involvement in economic activities as in the case of the Subprime Mortgage financial crisis. The three ideas of wealth distribution that require the circulation of property in both local and transnational domains become very relevant to see the imbalances that occur in the world today as the United Nations Development Program (UNDP) said as many as 20% of the rich in the world are enjoying 86% of world wealth, while 80% of the world's poor enjoy only 14% of the world's wealth. Keywords: Relevance, Capitalism Failure, Baqir Sadr Thought